2013
DOI: 10.3892/ijo.2013.2148
|View full text |Cite
|
Sign up to set email alerts
|

S(+)-ibuprofen destabilizes MYC/MYCN and AKT, increases p53 expression, and induces unfolded protein response and favorable phenotype in neuroblastoma cell lines

Abstract: Neuroblastoma is a common pediatric solid tumor that exhibits a striking clinical bipolarity favorable and unfavorable. The survival rate of children with unfavorable neuroblastoma remains low among all childhood cancers. MYCN and MYC play a crucial role in determining the malignancy of unfavorable neuroblastomas, whereas high-level expression of the favorable neuroblastoma genes is associated with a good disease outcome and confers growth suppression of neuroblastoma cells. A small fraction of neuroblastomas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 30 publications
1
7
0
Order By: Relevance
“…Similar to its mechanism of action in cancer cells, we observed that ibuprofen alters both proliferation and cell death in human fetal ovary. At a molecular level, studies in several cell lines have suggested a TP53dependent mechanism of ibuprofen toxicity that also involves an increase in the expression of CDKN1A (also known as p21) (Bonelli et al, 2011;Ikegaki et al, 2014;Janssen et al, 2008;Tsai et al, 2004). We found similar increases in TP53 and CDKN1A expression in the human fetal ovary after exposure to ibuprofen, suggesting that ibuprofen toxicity in the human fetal ovary may use a similar signaling pathway, and may act on molecular targets placed at the crossroad of proliferation and cell death.…”
Section: Ibuprofen Impacts the Growth Of The Human Fetal Ovarysupporting
confidence: 62%
“…Similar to its mechanism of action in cancer cells, we observed that ibuprofen alters both proliferation and cell death in human fetal ovary. At a molecular level, studies in several cell lines have suggested a TP53dependent mechanism of ibuprofen toxicity that also involves an increase in the expression of CDKN1A (also known as p21) (Bonelli et al, 2011;Ikegaki et al, 2014;Janssen et al, 2008;Tsai et al, 2004). We found similar increases in TP53 and CDKN1A expression in the human fetal ovary after exposure to ibuprofen, suggesting that ibuprofen toxicity in the human fetal ovary may use a similar signaling pathway, and may act on molecular targets placed at the crossroad of proliferation and cell death.…”
Section: Ibuprofen Impacts the Growth Of The Human Fetal Ovarysupporting
confidence: 62%
“…However, preclinical studies demonstrated that NSAIDs are also effective in inhibiting the proliferation of a wide range of cancer cells in vitro, either alone or in combination with other cancer therapies. This is further supported by clinical trials demonstrating that long-term use of NSAIDs, including ibuprofen, significantly reduces the risk of colorectal, breast, lung, prostate and gastric cancer and inhibits proliferation of cancer cells, including glioma, neuroblastoma and bladder cancer cells (Baron and Sandler, 2000;Ulrich et al, 2006;Johnson et al, 2010;Ikegaki et al, 2014;Chai et al, 2015;Fajardo and Piazza, 2015;Leidgens et al, 2015), thus increasing the interest for a novel therapeutic application of these drugs. However, this observation raises the question whether the inhibition of cell proliferation mediated by NSAIDs is also observed in non-malignant cells, with the consequence that the drug treatment results in delayed regeneration of tissues following injury.…”
Section: Discussionmentioning
confidence: 83%
“…Inhibition of COX enzymes has been shown to inhibit neuroblastoma cell survival in vitro and to inhibit tumour growth in vivo . Indeed, COX‐2 inhibitors attenuated cell viability in neuroblastoma cells.…”
Section: Discussionmentioning
confidence: 99%
“…In earlier studies, Rasmuson et al demonstrated that exogenous PGE 2 enhanced viability of MYCN-amplified SK-N-BE(2) neuroblastoma cells, suggesting that PGE 2 is involved in neuroblastoma cell viability independent of amplification of MYCN [4]. Inhibition of COX enzymes has been shown to inhibit neuroblastoma cell survival in vitro [7,42] and to inhibit tumour growth in vivo [5]. Indeed, COX-2 inhibitors attenuated cell viability in neuroblastoma cells.…”
mentioning
confidence: 99%